How LEM-based RBE and dose-averaged LET affected clinical outcomes of sacral chordoma patients treated with carbon ion radiotherapy - Molinelli, Silvia; Magro, Giuseppe; Mairani, Andrea; Allajbej, Albina; Mirandola, Alfredo; Chalaszczyk, Agnieszka; Imparato, Sara; Ciocca, Mario; Fiore, Maria Rosaria; Orlandi, Ester (Radiotherapy and oncology, 2021)
Purpose/objective - To understand the role of relative biological effectiveness (RBE) and dose-averaged linear energy transfer (LETd) distributions in the treatment of sacral chordoma (SC) patients with carbon ion radiotherapy (CIRT). - Material/methods - Clinical plans of 50 SC patients consecutively treated before August 2018 with a local effect model-based optimization were recalculated with the modified microdosimetric kinetic RBE model (mMKM). Twenty-six patients were classified as progressive disease and the relapse volume was contoured on the corresponding follow-up diagnostic sequence. The remaining 24 patients populated the control group. Target prescription dose (DRBE|50%), near-to-minimum- (DRBE|95%) and near-to-maximum- (DRBE|2%) doses were compared between the two cohorts in both RBE systems. LETd distribution was evaluated for in-field relapsed cases with respect to the control group. - Results - Target DMKM|50% and DMKM|95% were respectively 10% and 18% lower than what we aimed at. Dosimetric evaluators showed no significant difference, in neither of the RBE frameworks, between relapsed and control sets. Half of the relapse volumes were located in a well-covered high dose region. On average, over these cases, median target LETd was significantly lower than the control cohort mean value (27 vs 30 keV/μm). Most notably, the volume receiving dose from high-LET particles (>50 keV/μm) lay substantially below recently reported data in the literature. - Conclusion - A combined multi model RBE- and LET-based optimization could play a key role in the enhancement of the therapeutic ratio of CIRT for large radioresistant tumors such as sacral chordomas.